The principles of sustainability - Dresner, Simon (Sterling, VA Earthscan, 2008)
At a time of increasingly rapid environmental deterioration and climate change, sustainability is one of the most important issues facing the world. Can we create a sustainable society? What would that mean? How should we set about doing it? How can we bring about such a profound change in the way things are organized? This text tackles these questions directly. It covers: historical development of the concept of sustainability; contemporary debates about how to achieve it; and obstacles and the prospects for overcoming them. This new fully revised edition covers the latest on the climate change front, particularly the advances in scientific understanding and political awareness of climate change. Other updates include more recent economic analyses, particularly the Stern Report, and the global shift away from faith in markets over the past five years.
Rev. ed. of: The principles of sustainability. 2002.
Keywords: Sustainable development